Anaemia prevalence among school children of southern districts of Karnataka - Shabadi, Nayanabai; Thomas, Jose Jom; D., Sunil Kumar; M. R., Narayana Murthy; M., Shwethashree; Gopi, Arun (International Journal Of Community Medicine And Public Health, 2019)
Background: Anaemia is a major health problem creating an extreme burden on public health, especially in developing countries. Globally, anaemia affects 1.62 billion people, which corresponds to 24.8% of the population. The government of India is implementing various programs to bring down the prevalence of anaemia including iron and folic acid supplementation to school going children. This study attempts to assess the prevalence of anaemia among school going children of first to the tenth standard, in rural and urban areas of Mysore and Chamarajanagara districts of southern part of Karnataka state, India. Methods: A cross sectional study was conducted in 50 selected schools of Mysore and Chamarajanagara districts for a period of one academic year, and 8719 students were evaluated for anaemia. The data was analyzed using appropriate software and statistical methods. Results: The prevalence of anaemia among school going children in Mysore and Chamarajanagar districts was 27.6%. While 22.7% of the girls showed the signs of anaemia, only 19.2% of boys showed anaemia. The prevalence of anaemia was high in rural areas than urban areas and maximum prevalence was seen among high school students followed by upper primary school students and lower primary school students. Conclusions: The total prevalence of anaemia among school children in Mysore and Chamarajanagara districts was 27.6%. The prevalence of anaemia was below the currently available national standards. This low prevalence could be attributed to the continuing care with yearly screening and iron and folic acid tablets provided to the study population under National Health Mission.